Trapping mechanisms in GaN‐based MIS‐HEMTs grown on silicon substrate. Issue 5 (4th February 2015) - Bisi, Davide; Meneghini, Matteo; Van Hove, Marleen; Marcon, Denis; Stoffels, Steve; Wu, Tian‐Li; Decoutere, Stefaan; Meneghesso, Gaudenzio; Zanoni, Enrico
<x xml:space="preserve">Abstract</x> In this work we report on the three dominant trapping mechanisms affecting the dynamic performance of a double‐heterostructure GaN‐based MIS‐HEMT grown on silicon substrate. In the OFF‐state, with high drain voltage and pinched‐off 2DEG, the dominant mechanism is the charge‐trapping in the gate‐drain access region caused by the transversal drain‐to‐substrate potential. This effect causes the dynamic increase of the ON‐resistance, and is positively temperature‐dependent, thus of great concern for high‐temperature operation. In the SEMI‐ON‐state, due to the presence of high VDS and relatively high IDS, an additional trapping mechanism emerges, involving the injection of hot electrons from the 2DEG into trap states located in the GaN‐buffer or in the AlGaN barrier. This mechanism, critical in hard‐switching operations, affects both the ON‐resistance and the VTH. Finally, when the gate is positively biased (gate overdrive state) trapping of electrons happens in the gate dielectric layer(s), leading to strong metastable VTH instabilities.